Phenotyping oil palm for drought adaptation using photosynthetic and root traits as indicators - Wong, Yick Ching (2025)
Oil palm is the highest oil producing crop of all other oil crops at present. It contributes the largest (37%) share to the global edible oil consumption. Malaysia and Indonesia are the two largest palm oil producing countries, which account for major (84%) palm oil in total world production. However, unpredictable and extreme weather conditions caused by external factors such as El Niño could make the production of oil palm in the future a challenge. The exposure of oil palm to various environmental stresses such as drought throughout its life cycle could cause yield loss up to 25%. Selection of oil palm materials that could withstand drought without compromising the yield production is crucial. The hypothesis is that it is possible to select drought tolerant oil palm genotypes at seedlings stage through combination of various phenotyping methods.